South Korea’s Response to Japan’s Export Restrictions on Semiconductor Materials - Butar Butar, Asido Mac Kenzie (Universitas Medan Area, 2025)
This study analyzes South Korea's strategic responses to Japan's 2019 export restrictions on three key chemicals vital to its semiconductor industry: fluorinated polyimide, photoresist, and hydrogen fluoride. Beyond filing a WTO complaint, South Korea pursued retaliatory actions—tightening trade regulations and initiating boycott movements—while strengthening its semiconductor sector through funding, tax incentives, and cross-sector collaboration. Employing a neo-Mercantilist framework and qualitative method, this research highlights how state-led industrial strategies serve as a tool of economic resilience and foreign policy, contributing to broader discussions in International Political Economy on government agencies in navigating trade disputes and securing technological sovereignty.